THE USE OF EDUCATIONAL SEISMOGRAPHS IN THE SEISMOLOGY SCHOOL NETWORK “EGELADOS” - Fermeli, G.; Vitsas, T.; Foundas, P.; Sokos, E.; Alexandropoulou, S.; Papatheodoropoulos, P.; Germenis, N.; Nikolaidis, A.; Zevgitis, T. (Bulletin of the Geological Society of Greece, 2010)
In this paper we attempt to describe the experience we gained, working with a specially designed seismograph as an educational device. It is a modern instrument with short period response, GPS timing and digital recording on personal computer. The installation was done in the frame of the local seismology school network, called “Egelados”. The knowledge of basic concepts of geology, physics and mathematics (Lower High School level - Gymnasium) is a prerequisite for the use of the instrument. Further research of the earthquake phenomenon and the analysis of the recorded data leads to didactic objectives in sciences and mathematics which are included in the Lyceum curriculum. The reliability test of the results obtained using the seismograph has, from the analysis students made, shown up to now declinations of the events magnitude of 0,2 - 0,4 when compared to magnitudes published by National Observatory of Athens-Institute of Geodynamics. Students’ constructions to overcome the calculation difficulties to find the exact location of epicentre are often proposed activating in this way their research mood. Up to now the use of the tool, in the framework of network “Egelados”, not only connects the participating schools but also gives the opportunity for further collaboration among teachers and students that have installed a similar instrument. Finally, everyday use of the seismograph reveals its drawbacks and provides ideas of enhancements.